The Negative Effects of the Separation Wall on the Architectural and Urban Heritage of Al-Quds - Mahmoud, Amira Mersal (Journal of Islamic Architecture, 2017)
The destruction of archaeological sites leads to big loss at the local and regional levels and any interruption to the past will have a negative impact on the present and the future. The preservation and protection of archaeological sites consists an economic, cultural and heritage impact for the nations. This study aims mainly to review the factors threating the destruction of archeological sites with an attempt to find the methods that reduce the threat and preserve what is left of the Palestinian remains. In additions, it includes an analytical study of the direct and indirect of the separation wall on the archeological sites in Al-Quds (Al-Quds 2020). The most important of these threats to the architectural heritage is the danger of the separation wall (The Al-Quds envelope). The study recommended the need for intensified efforts by concerned Palestinian authorities and institutions, especially the Ministry of Tourism and Antiquities to face the wall and its negative effects on archaeological sites on one hand and to put the protection and preservation of archaeological sites within their priorities on the one hand. Others, because of the economic and cultural importance of these sites, which affect the identity of the architecture.Â Â